SIC ET NON : KEBEBASAN DAN PEMBATASAN HAK KEMUDAHAN DAN PERLAKUAN KHUSUS - Dhia Al Uyun (Yuridika, 2016)
Sic et Non. Yes and no. Freedom and restriction of the essence of HKPK. Both are located face-to-face. Every country has a unique character in implementing and synthesizing. This matter will be discussed in this article. The main problem is the ratio legis HKPK in the constitution. In Indonesia, the ratio legis is constitutional rights. Ratio Legis HKPK in Indonesia is in the framework of the realization of gender justice it is seen in various minutes of the amendment formulation meeting. As part of human rights, HKPK emerges under a forum agreement to be an integral part of human rights. However, the textual HKPK does not limit the HKPK on gender differences. The decision of the Constitutional Court to legitimize the application of HKPK in cases of gender differences. In India and Pakistan is fundamental rights. In Germany leads to individualistis. In United States showed unwritten constitution. Finally in South Africa show the priority in the equality. Secondly, The freedom and restriction are both, sythese as morallity and realize by rule.